Tetramer-Based Enrichment of Preexisting Anti-AAV8 CD8+ T Cells in Human Donors Allows the Detection of a TEMRA Subpopulation - Vandamme, Céline; Xicluna, Rebecca; Hesnard, Leslie; Devaux, Marie; Jaulin, Nicolas; Guilbaud, Mickaël; Le Duff, Johanne; Couzinié, Célia; Moullier, Philippe; Saulquin, Xavier; Adjali, Oumeya (Frontiers in Immunology, 2020)
Pre-existing immunity to AAV capsid may compromise the safety and efficiency of rAAV-mediated gene transfer in patients. Anti-capsid cytotoxic immune responses have proven to be a challenge to characterize because of the scarcity of circulating AAV-specific CD8+ T lymphocytes which can seldom be detected with conventional flow cytometry or ELISpot assays. Here, we used fluorescent MHC class I tetramers combined with magnetic enrichment to detect and phenotype AAV8-specific CD8+ T cells in human PBMCs without prior amplification. We showed that all healthy individuals tested carried a pool of AAV8-specific CD8+ T cells with a CD45RA+ CCR7- terminally-differentiated effector memory cell (TEMRA) fraction. Ex vivo frequencies of total AAV-specific CD8+ T cells were not predictive of IFNγ ELISpot responses but interestingly we evidenced a correlation between the proportion of TEMRA cells and IFNγ ELISpot positive responses. TEMRA cells may then play a role in recombinant AAV-mediated cytotoxicity in patients with preexisting immunity. Overall, our results encourage the development of new methods combining increased detection sensitivity of AAV-specific T cells and their poly-functional assessment to better characterize and monitor AAV capsid-specific cellular immune responses in the perspective of rAAV-mediated clinical trials.